Propensity score-matched analysis of the ‘2+2’ parathyroid strategy in total thyroidectomy with central neck dissection - Gong, Hao; Yao, Simei; Jiang, Tianyuchen; Yang, Yi; Jiang, Yuhan; Wu, Zhujuan; Su, Anping (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the clinical efficacy of the “2+2” strategy (preserving 2 superior glands in situ and autotransplanting 2 inferior glands) in patients with papillary thyroid carcinoma (PTC) undergoing total thyroidectomy (TT) with bilateral central lymph node dissection (BCLND), using propensity score matching (PSM) to control confounding.Materials and methodsA retrospective cohort of 1,099 PTC patients treated with TT+BCLND at West China Hospital (2017–2023) was analyzed. After 1:1 PSM, 592 patients (296 per group) were included. Outcomes included temporary hypoparathyroidism (THP), permanent hypoparathyroidism (PHP), and postoperative PTH, calcium (Ca), and vitamin D (VitD) levels. Logistic regression identified predictors of THP and PHP.ResultsAfter matching, baseline characteristics were comparable. The “2+2” group had longer operative time (150 vs. 123 min, p<0.01), higher THP incidence (72.97% vs. 48.31%, p<0.01), and lower PHP incidence (0.68% vs. 3.72%, p = 0.03). PTH and Ca levels dropped more on postoperative day 1 in the “2+2” group but recovered more rapidly between day 1 and month 1. By month 12, levels converged in both groups. Parathyroid autotransplantation was an independent risk factor for THP (OR = 2.476, p<0.01) but protective against PHP (OR = 0.139, p = 0.02). Tumor size was also associated with THP risk (OR = 1.424, p = 0.04).ConclusionThe “2+2” strategy increases short-term THP risk but significantly reduces long-term PHP. Rapid biochemical recovery supports the functional viability of autotransplanted glands. This approach may offer a safe and effective strategy for parathyroid management in high-risk thyroid surgeries.